2010
DOI: 10.5539/cis.v3n2p235
|View full text |Cite
|
Sign up to set email alerts
|

Financial Sustainability Issues in Malaysia’s Telecentres

Abstract: Telecentres plays an important role in bridging digital divide in Malaysia. A study was conducted to identify the issues of financial sustainability on 132 telecentres in Malaysia. The study focused on TCs in four regions of Malaysia Peninsular (northern, central, southern and eastern). Questionnaires were sent to the telecentres' operators. The results prove that financial support is critical in operating and maintaining the centers. The costs incurred in running telecentres involve the costs for promotion, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…Users of the telecentre among agro-pastoralists expressed satisfaction with the fact that the ICTs services were accessible to agro-pastoralists community members, who could now make use of ICTs and had the opportunity to communicate with the rest of the world for livelihoods and basic services support (Etta and Parvyn-Wamahiu, 2003: Ibrahim et al, 2010: Morton & Kerven, 2013.…”
Section: N=number Of Respondentsmentioning
confidence: 99%
“…Users of the telecentre among agro-pastoralists expressed satisfaction with the fact that the ICTs services were accessible to agro-pastoralists community members, who could now make use of ICTs and had the opportunity to communicate with the rest of the world for livelihoods and basic services support (Etta and Parvyn-Wamahiu, 2003: Ibrahim et al, 2010: Morton & Kerven, 2013.…”
Section: N=number Of Respondentsmentioning
confidence: 99%
“…The connectivity needs of rural residents are being addressed in part through the telecenter program, which established forty-two telecenters from 2000 to 2003. However, the financial sustainability of rural telecenters is often challenged ( Proenza 2001 ) and this is as true in Malaysia as elsewhere ( Ibrahim, Yasin, and Dahalin 2010 ). It is therefore important to ascertain whether government sponsorship of telecenters is worthwhile, by asking whether telecenters are making a positive impact on people ' s lives.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that a lack of financial support has caused many telecentres to face sustainability problems in Malaysia (Norizan & Jalaluddin, 2008). According to Ibrahim et al (2010), financial support is the key element for operating and maintaining telecentres. Telecentres are generally dependent on public funds at least in their initial stages.…”
Section: Systematic Financial Planningmentioning
confidence: 99%